A review of the Malagasy endemic genera Anaceros, Hovanoceros and Malgaceros (Opiliones: Laniatores: Biantidae) - Mamani, Claudia Vanesa (2020)
Anaceros Lawrence, 1959, Hovanoceros Lawrence, 1959 and Malgaceros Lawrence, 1959, are three biantid genera endemic to Madagascar. Anaceros was originally described to accommodate four species, whereas Hovanoceros and Malgaceros were described as monotypic. Before now, species in these genera were known only from the original descriptions, in which important taxonomic characters (e.g. male genital morphology) were not described. After examining 250 specimens from the California Academy of Sciences collection, we provide a redescription of all previously known species and describe six new species. As well as describing the exomorphology, we provide a detailed description of the male genitalia, and of microdetails documented through Scanning Electron Microscopy. Our results show that the characters previously used to define the genera (e.g. ocularium size) are highly variable among species and have no utility for generic delimitation. We propose Hovanoceros and Malgaceros as junior synonyms of Anaceros and consequently propose their new combinations respectively. Also, we emend the diagnosis of the genus Anaceros. This study reveals just a small part of the rich and uncharted diversity of litter-dwelling Malagasy opilionids. Because of the high level of micro-endemicity observed, we predict that many new species of this group remain to be discovered on the island.